Analyzing the impact of public capital on private capital productivity in a panel of African nations - Elhadj Ezzahid; Hamid Rafik (Economies, 2024)
This research contributes to the ongoing discourse concerning the efficiency of public capital and its influence on the productivity of private capital and total factor productivity within African economies. Employing the standard production approach, we include public capital as a distinct input to assess its specific impact on output growth and the enhancement of total factor productivity. We argue that public capital, predominantly manifesting through infrastructure, constitutes an indispensable element for fostering growth. Fundamental to the productivity of private capital is its reliance on a sufficient stock of public infrastructure for operational efficiency. Our empirical analysis reveals that public capital exhibits a substantive long-term influence on output growth and the productivity of private capital. However, in the short term, the discernible impact of public capital is less pronounced. Moreover, while public capital emerges as a noticeable factor in output growth, its influence on total factor productivity remains relatively subdued.
Keywords: 330; Africa; economic growth; public capital; total factor productivity